2014
DOI: 10.1007/s10531-014-0778-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and dispersal ecology of Lobaria pulmonaria in the largest primeval beech forest of Europe

Abstract: Occupancy and density of the epiphytic lichen L. pulmonaria were studied in the mountains of Uholka-Shyrokyi Luh (Ukraine), which include the largest primeval beech forest in Europe. The lichen occupancy was assessed on 314 plots laid out on a systematic grid. Additional data on population density were collected from 483 trees growing both, on and between these plots. The trees harbouring L. pulmonaria were distributed very sparsely within Uholka-Shyrokyi Luh, and occupy nearly 10 % of the studied perimeter. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 59 publications
(83 reference statements)
1
21
0
Order By: Relevance
“…During our field trips held in 2014 in the Rhodopes, the number of detected individuals varied from 50 thalli of juvenile lung lichen in bark of one old beech tree at an altitude of 1660 m in Mantaritsa Reserve (Figure 2), till 5 juvenile individuals in the region of Cigov Chark, noticed on bark of single beech tree and from 1-20 mature individuals seen at altitudes between 1350 and 1440 m, respectively. It is in agreement with conclusions recently published (28), stating that the presence of the lichen thalli, i.e. the occupation of the trees by the lung lichen, not only depends on the age of trees and air humidity, but also is primaly reflected by canopy cover and the altitude ranges above sea level.…”
Section: Discussionsupporting
confidence: 93%
“…During our field trips held in 2014 in the Rhodopes, the number of detected individuals varied from 50 thalli of juvenile lung lichen in bark of one old beech tree at an altitude of 1660 m in Mantaritsa Reserve (Figure 2), till 5 juvenile individuals in the region of Cigov Chark, noticed on bark of single beech tree and from 1-20 mature individuals seen at altitudes between 1350 and 1440 m, respectively. It is in agreement with conclusions recently published (28), stating that the presence of the lichen thalli, i.e. the occupation of the trees by the lung lichen, not only depends on the age of trees and air humidity, but also is primaly reflected by canopy cover and the altitude ranges above sea level.…”
Section: Discussionsupporting
confidence: 93%
“…The altitudinal distribution of L. pulmonaria showed a clear bimodal pattern in the primeval landscape we studied (Nadyeina et al . ). Altitude also explains the diversity and composition of epiphytic lichens (Dymytrova et al .…”
Section: Discussionmentioning
confidence: 97%
“…We have showed recently that L. pulmonaria prefers relatively open stands in the forest landscape at higher altitudes and survives in the closed canopy of lowland valley growing high on tree trunks to receive the necessary level of insolation (Nadyeina et al . ). Our genetic analyses further revealed that different types of habitats, related to altitude, were colonized by different gene pools.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations